Social democracy as a development strategy - Karl Ove Moene (University of Oslo, Department of Economics, 2003)
Social democracy, it is often said, is nice but pricey. Whatever its merits in the rich countries of Western Europe, social democracy is frequently dismissed as an infeasible model for developing countries. Based on generosity towards the poor and protection against market competition, the argument goes, social democracy is only possible in consensual, homogeneous and affluent societies with an extraordinary commitment to equality. In third world countries that are conflict-ridden, heterogeneous and poor, does the social democracy have any relevance? In this article we offer a more agnostic view of the feasibility of the social democratic model of development in the third world. First, we argue that consensus, homogeneity, and affluence are products of the social democratic model, not prerequisites. Second, we claim that the central social democratic policy as a development model was the policy of wage compression attained through highly centralized wage-setting institutions. Third, we argue that the economics benefits of wage compression would be as significant in South Africa, Brazil or India today as they were in the Nordic countries between 1935 and 1970. The political feasibility of a policy of wage compression, however, is open to doubt, hence our agnosticism regarding whether or not the social democratic road to affluence can be repeated. In this paper we consider social democracy to be model of development rather than an end state. In particular, we will not enter into the debate regarding the future prospects of social democracy in Western Europe within the context of European economic integration, a common currency, an aging population and the ever increasing cost of providing the best health care that money can buy. The achievements of social democracy as a development strategy in terms of combining the socialist virtues of equality and security without losing the capitalist virtues of economic efficiency and technological dynamism are not seriously in dispute. What are disputed are the answers to the following questions: What was the contribution of specifically social democratic policies to the high level of affluence and equality in Northern Europe today. Would the policies that successfully promoted development in Northern Europe be equally effective and feasible in the third world in the context of an increasingly integrated global economy?
Keywords: O10; P20; 330; Development strategy; social democracy; Sozialdemokratie; Sozialstaat; Entwicklungsstrategie